Criminal liability for the use of artificial intelligence in Indonesia - Hadi Purnomo (Jurnal Info Sains : Informatika dan Sains, 2023)
Artificial intelligence (AI) has become an integral part of various sectors in Indonesia, making a significant contribution to increasing efficiency, productivity and innovation. However, this rapid development has also given rise to various legal challenges, especially regarding criminal liability for the use of AI. This research aims to analyze the legal framework that applies in Indonesia regarding policies and criminal liability for the use of artificial intelligence. This research uses normative legal research methods through a statutory approach. The research results show that the concept of criminal liability that applies to individuals is not fully applicable to artificial intelligence (AI). As an electronic system, AI does not have the ability to understand the consequences of its actions, recognize violations of societal norms, or determine its will independently. In the Indonesian legal framework, criminal responsibility is placed more heavily on humans who create and control AI, indicating the need for clearer legal regulations to address ethical and legal issues that arise as AI technology develops.